Epistasis-driven identification of SLC25A51 as a regulator of human mitochondrial NAD import - Girardi, Enrico; Agrimi, Gennaro; Goldmann, Ulrich; Fiume, Giuseppe; Lindinger, Sabrina; Sedlyarov, Vitaly; Srndic, Ismet; Gürtl, Bettina; Agerer, Benedikt; Kartnig, Felix; Scarcia, Pasquale; Di Noia, Maria Antonietta; et al. (Nature communications, 2020)
About a thousand genes in the human genome encode for membrane transporters. Among these, several solute carrier proteins (SLCs), representing the largest group of transporters, are still orphan and lack functional characterization. We reasoned that assessing genetic interactions among SLCs may be an efficient way to obtain functional information allowing their deorphanization. Here we describe a network of strong genetic interactions indicating a contribution to mitochondrial respiration and redox metabolism for SLC25A51/MCART1, an uncharacterized member of the SLC25 family of transporters. Through a combination of metabolomics, genomics and genetics approaches, we demonstrate a role for SLC25A51 as enabler of mitochondrial import of NAD, showcasing the potential of genetic interaction-driven functional gene deorphanization. Maintenance of a mitochondrial NAD+ pool is critical for cellular life, yet the existence and identity of the transporter responsible for mitochondrial NAD+ uptake was unknown until recently. Here, the authors use genomic, genetic, and metabolomic approaches to demonstrate that SLC25A51 controls NAD+ mitochondrial levels and is the functional homolog of the yeast mitochondrial NAD+ transporter.